5 Answers | Add Yours
Well first you have to take out the divided by 4, so for that you multiply both sides by 4
((x+2)/4) x 4= 4x-4
Now you would move all the variables on one side
Now simplify the equation and you would be able to get
To get the final answer just divide by 3 and x=2
As always we will use the PEMDAS/BODMAS order of operations through which first we open brackets, then multiply then divide then add and at last subtract.
Multiply both sides with 4;
Open RHS bracket by multiplying both the values with 4;
Now divide both sides with 3;
Therefore the answer is 2.
Hence it is Solved!
`(x + 2)/4 = x - 1`
To simplify this we need to follow the order of operations, i.e BODMAS / PEMDAS, first we need to multiply both sides by 4,
`(x + 2)/4 * 4 = 4(x-1)`
`x + 2 = 4x - 4`
`x + 2 - 2 = 4x - 4 - 2`
`x - 4x = 4x - 4x - 6`
`-3x = -6`
`-3x/-3 = -6/-3`
`x = 2 Answer.`
The equation (x+2)/4=x-1 has to be solved for x.
Multiply both sides by 4
x + 2 = 4*(x - 1)
x + 2 = 4x - 4
Add -2 to both the sides
x = 4x - 6
Subtract 4x from both the sides
-3x = -6
Divide both the sides by -3
x = 2
The solution of the equation (x+2)/4=x-1 is x = 2
We’ve answered 319,674 questions. We can answer yours, too.Ask a question